Implemantation of world experience in credit programs of development of logistics infrastructure, logistics systems and technologies - Kolodizieva, Tetiana; Kotsiuba, Olena (Technology audit and production reserves, 2017)
Transport and logistics infrastructure is an indicator of the state's readiness to cooperate with international partners, to expand contacts etc. The quality of the logistics system within the company plays a significant role in profit making. The object of the study is the process of lending for the development of logistics infrastructure. One of the biggest weaknesses is that the quality of Ukrainian transport infrastructure is not satisfactory, according to a study by the World Bank. And there is no practice of lending programs for the development of logistics infrastructure by Ukrainian or foreign banks in Ukraine. Therefore, an analysis of the foreign experience of lending to the development of logistic infrastructure was conducted. The experience of the Philippines, USA, India and Bulgaria is considered. According to the results of the analysis of international lending programs, a structurally-functional model of the process of lending for the development of logistic infrastructure development using the CASE-method in the ERwin Process Modeler software product according to the IDEF0 standard was constructed. This model has made it possible to identify the main stages of funding for the development of logistic infrastructure and to demonstrate the interrelations between participants and the methodological support of this process. The Ukrainian government should pay attention to such positive moments of world experience in transport infrastructure as: – attraction of foreign investors specializing in innovations; – improvement of the railway infrastructure; – construction of highways; – improving the quality of roads, etc. This will strengthen international contacts with Ukraine, increase energy efficiency of production and significantly reduce the burden on the basis of Ukraine's transport and transport components